Dilalah al-Ma’na al-Siyaqi li Kalimah al-Ajal fi al-Quran al-Karim - Mabrurrosi, Mabrurrosi; Yakin, Nurul (Dzil Majaz: Journal of Arabic Literature, 2023)
The Qur’an is a word of God that was revealed to a Prophet, may God’s prayers and peace be upon him, who emerges from darkness into light, and the Qur’an is a guide for man to longevity and internal and external happiness in long life. Semantics is the science that studies meaning, and part of the language, and meaning is six approaches, gifted by the contextual theory . The questions in this research are the number of a word denoting the term in the Holy Qur’an and the contextual meaning of the term in the Holy Qur’an. The objectives of the research are to know the word term in the Holy Quran and to know the significance of the contextual meaning of the word term in the Holy Quran. The research method used is qualitative because all data are in word form. And the results of the research: the word term in the Holy Quran is 48 verses, and the number of the word term is fifty-six. The contextual meaning of the word term in the Holy Qur’an has four meanings: in the sense of time, in the sense of the specified, in the sense of death, and in the sense of cause.